'How Belfast got the blues': Towards an alternative history. (18th December 2017) - McLaughlin, Noel; Braniff, Joanna
Abstract : This article offers a revisionist history of a key period of Belfast and Northern Ireland's music scene in the 1960s: the emergence of Them and Van Morrison and the attendant 'legend' of the group's residency in the city's Maritime Hotel. This formative moment is, somewhat surprisingly, under-explored in popular music studies, and the article seeks to address this relative absence. Van Morrison's biographies are a vital resource here, and—via discourse analysis—we trace the emergence of a dominant narrative and assess its ideological implications, before moving on to analyse Them's breakthrough single and related promotional materials. In so doing, we connect the scene that the group both emerged from and represented, to broader popular musical trends, as well as considering how the story of Them's emergence is supported and framed in contemporary heritage initiatives. The article argues that the myth of Them, Morrison and the Maritime has obscured other ways of approaching the period, and we conclude with a counterhistory by considering an earlier blues/jazz scene in the city and how this might shape an orthodox narrative.